2007
DOI: 10.1120/jacmp.v8i4.2439
|View full text |Cite
|
Sign up to set email alerts
|

Using an onboard kilovoltage imager to measure setup deviation in intensity‐modulated radiation therapy for head‐and‐neck patients

Abstract: The purpose of the present study was to use a kilovoltage imaging device to measure interfractional and intrafractional setup deviations in patients with head‐and‐neck or brain cancers receiving intensity‐modulated radiotherapy (IMRT) treatment.Before and after IMRT treatment, approximately 3 times weekly, 7 patients were imaged using the Varian On‐Board Imager (OBI: Varian Medical Systems, Palo Alto, CA), a kilovoltage imaging device permanently mounted on the gantry of a Varian 21EX LINAC (Varian Medical Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…The results of the sub-millimetre magnitude of intra-fraction movement measured in this study were found to be in accordance with those findings from previous studies [7,8,15]. The overall magnitude of the intra-fraction movement of 0.3 mm in our study was similar to the intra-fraction movement of 0.2 mm reported by Suzuki et al [7].…”
Section: Discussionsupporting
confidence: 95%
“…The results of the sub-millimetre magnitude of intra-fraction movement measured in this study were found to be in accordance with those findings from previous studies [7,8,15]. The overall magnitude of the intra-fraction movement of 0.3 mm in our study was similar to the intra-fraction movement of 0.2 mm reported by Suzuki et al [7].…”
Section: Discussionsupporting
confidence: 95%
“…A rectangular region of interest was set by the physician in the AP and lateral views on the initial day of setup and was replicated for matching purposes throughout treatment (Djodjevic 2007, Fox et al 2006). The kV x-ray OBI/automatching hardware/software system has been presented previously (Kim et al 2008, Mechalakos et al 2007, Sorcini and Tilikidis 2006), in phantom verification tests, and is reported to have demonstrated ‘overall uncertainty in the positioning of known offsets [of] approximately 1.4 mm for most clinical cases’ (Fox et al 2006). Automatic KVX to DRR (2D–2D) registration was also accomplished using the same manufacturer-supplied software package (Varian OBI 1.3/Varian Vision, Varian Medical Systems, Palo Alto, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Rigid errors, such as setup, have been extensively studied. Mechalakos et al [6]. for instance evaluated the interfraction and interfraction errors in treatments of HNC and compared their results with previous studies from others authors.…”
Section: Introductionmentioning
confidence: 99%